"Understanding Our Peers": A Naturalistic Program to Facilitate Social Inclusion for Children with Autism in Mainstream Early Childhood Services. Issue 5 (3rd September 2022) - Balaz, Lidija; Byrne, Mitchell K.; Miellet, Sebastien
ABSTRACT: This study evaluated the effects of an early education inclusion program for children with autism: 'Understanding our Peers; the Early Years'. A series of children's books were created outlining the core behavioural features of autism and how the characters in the books were able to understand these behaviours and accommodate the needs of the child with autism. The books were read to the entire preschool centre cohort across a 12-week period, supported by educator discussion and engagement with the children. Naturalistic behavioural observations were made of the social encounters of 24 preschool children with autism aged between 44 months and 67 months. The intervention was applied in nine mainstream centres with 523 typically developing children enrolled. Results indicated that the program resulted in an increase in positive interactions between the child with autism and their typically developing peers and concomitantly reduced the incidence of negative encounters for the child with autism. Overall, findings provide preliminary evidence supporting the efficacy of an anti-stigma program to support social inclusion of children with autism in mainstream early educational environments.